Anterior cervical discectomy and fusion versus anterior cervical corpectomy and fusion in the treatment of multilevel cervical spondylotic myelopathy: systematic review and a meta-analysis - Wen ZQ; Du JY; Ling ZH; Xu HD; Lin XJ (Dove Medical Press, 2015)
Zhi-qiang Wen,1 Jing-yu Du,1 Zhi-heng Ling,1 Hai-dong Xu,2 Xiang-jin Lin1 1Department of Orthopaedics, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, 2Department of Spine Surgery, Jinling Hospital, School of Medicine, Nanjing University, Nanjing, People’s Republic of China Background: To date, the decision to treat multilevel cervical spondylotic myelopathy (CSM) with anterior cervical discectomy and fusion (ACDF) or anterior cervical corpectomy and fusion (ACCF) remains controversial. Therefore, we conducted a meta-analysis to quantitatively determine the efficacy of ACDF and ACCF in the treatment of multilevel CSM. Methods: We searched several databases for related research articles published in English or Chinese. We extracted and assessed the data independently. We determined the pooled data, data heterogeneity, and overall effect, respectively. Results: We identified 15 eligible studies with 1,368 patients. We found that blood loss and numbers of complications during surgery in ACDF were significantly less that in ACCF; however, other clinical outcomes, such as operation time, bone fusion failure, post Japanese Orthopedic Association scores, recovery rates, and visual analog scale scores between ACDF and ACCF with multilevel CSM were not significantly different. Conclusion: Our results strongly suggest that surgical treatments of multilevel CSM are similar in terms of most clinical outcomes using ACDF or ACCF. Keywords: meta-analysis, therapy, anterior cervical discectomy and fusion, anterior cervical corpectomy and fusion, cervical spondylotic myelopathy